Analytic processes for school leaders - Richetti, Cynthia T. (Association for Supervision and Curriculum Development, 2001)
How do you make a decision? How do you know you've made a good one? Whether you're a 7th grade student selecting a science fair project, or a school board choosing a superintendent, the basic requirements of decision making are the same. You need information and the ability to analyze that information effectively. This is rational thinking, and it doesn't happen by accident. It's an acquired skill. Analytic Processes for School Leaders describes four rational-thinking processes: . Decision analysis . Potential problem analysis . Problem analysis . Situation appraisal The authors explain how educators can use these analytic processes to handle four common types of situations: when something goes wrong, when we need to make a choice, when we need to implement a change, and when we need to better understand a complex issue. Using these processes teaches rational thinking and benefits administrators, teachers, and students. Throughout the book, extended examples in administrative and classroom settings translate theory into practice, taking the reader step-by-step through each process. Key questions guide the reader. The authors describe how breaking the thinking process down into steps helps us reach better conclusions because we can understand, fine-tune, and improve our own approaches; communicate our rationale to others; more effectively involve others in solving problems; and teach these skills to others. Cynthia Richetti is vice president and Benjamin Tregoe is founder and chair of the Tregoe Education Forum, a nonprofit organization created to bring critical-thinking skills to K61485;12 students and school administrators. Tregoe is also cofounder of Kepner-Tregoe, Inc., an international management consulting firm.